Microsoft Office Training 2016 At SMK PBD Penerbangan - Nurhayati Nurhayati; Frinto Tambunan (JUDIMAS, 2021)
Technological developments from time to time must be aligned with the development of human resources as users of the technology. If seen until now, quite a lot of technology is used both in schools and other public places. Even technology has been considered as a primary need in this modern era. Good communication technology, computing, household appliances and so on. Many things are managed with the help of IT to streamline the process of completing a job. This is in contrast to the fact that many technology users (brainware) are not fully prepared. For that we start from school and teach it as early as possible through workshop activities by teaching software that will help them know in terms of managing school budgets, administration, finance, presentations to reporting related to IT. There are also many software available to manage it such as Microsoft Office. Consisting of Ms. Office 2016, Ms. Office Excel and more. In the service activities carried out at the SMK PBD Penerbangan. Students are taught to know and be able to operate the Microsoft Office 2016 and WIN 10 software so that they can be useful in the future. Especially when they plunge into the world of work.